Pradhan Mantri Jan Dhan Yojana (PMJDY) : Analyzing Performance Using Financial Inclusion Indicators - Thakur, Shalvi (Arthshastra Indian Journal of Economics & Research, 2022)
PMJDY (Pradhan Mantri Jan Dhan Yojana), one of India’s most popular financial inclusion programs, was touted as a potential game-changer that could transform decades of dreams of attaining complete financial inclusion into a reality. This article tried to verify these claims and closely examined the various financial inclusion indicators which should have changed after the introduction of this program. It was inferred that despite several flaws in its implementation, PMJDY generated a tremendous number of bank accounts for those who had none. The study found that, remarkably, females own more than half of the accounts. However, account usage among females is low due to fewer employment opportunities. Women empowerment and raising entrepreneurial spirit are some solutions to allow women to save money in the formal banking system. It has become feasible to make direct cash transfers to vulnerable people’s PMJDY accounts whenever necessary. Increased access to financial products can lift many people out of perpetual poverty. It is too early, however, to comment on the reduction of poverty and inequality in India due to PMJDY. PMJDY has not affected the C-D Ratio; an increase in profitable credit deployment is imperative for increasing bank profits. Another caveat is the low awareness and widespread financial and technological illiteracy preventing full-fledged access to the program’s benefits. Learning from the financial programs of other LMICs, the periodic assessment of PMJDY, and solving implementation problems are necessary for the program’s long-term sustainability.